C65 POST–DISCHARGE ARRHYTHMIC RISK STRATIFICATION OF PATIENTS WITH ACUTE MYOCARDITIS AND LIFE–THREATENING VENTRICULAR TACHYARRHYTHMIAS. (18th May 2022) - Gentile, P; Merlo, M; Peretto, G; Ammirati, E; Sala, S; Della Bella, P; Aquaro, G; Imazio, M; Potena, L; Campodonico, J; Foà, A; Raafs, A; et al.
Abstract: Aims: The outcomes of patients presenting with acute myocarditis and life–threatening ventricular arrhythmias (LT–VA) are unclear. The aim of this study was to assess the incidence and predictors of recurrent major arrhythmic events (MAEs) after hospital discharge in this patient population. Methods and Results: We retrospectively analysed 156 patients (median age 44 years; 77% male) discharged with a diagnosis of acute myocarditis and LT–VA from 16 hospitals worldwide. Diagnosis of myocarditis was based on histology or the combination of increased markers of cardiac injury and cardiac magnetic resonance (CMR) Lake Louise criteria. MAEs were defined as the relapse, after discharge, of sudden cardiac death or successfully defibrillated ventricular fibrillation, or sustained ventricular tachycardia (sVT) requiring implantable cardioverter–defibrillator therapy or synchronized external cardioversion. Median follow–up was 23months [first to third quartile (Q1–Q3) 7–60]. Fifty–eight (37.2%) patients experienced MAEs after discharge, at a median of 8 months (Q1–Q3 2.5–24.0 months; 60.3% of MAEs within the first year). At multivariable Cox analysis, variables independently associated with MAEs were presentation with sVT [hazard ratio (HR) 2.90, 95% confidence interval (CI) 1.38–6.11]; late gadolinium enhancement involving ≥2 myocardial segments (HR 4.51, 95% CI 2.39–8.53), and absence of positive short–tau inversion recovery (STIR) (HR 2.59, 95% CI 1.40–4.79) at first CMR. Conclusions: In this international multicentre study, patients discharged free from HTx or LVAD after an acute myocarditis complicated by LT–VA had a recurrence of MAEs during follow–up of 37.2%, after a median time of 8 months. Initial CMR pattern and sVT at presentation stratify the risk of arrhythmia recurrence.